Performance Evaluation of a Condenser at a Combined Cycle Power Plant Using the LMTD Method - Putut Jaya Swardhamana; Nanang Ruhyat; Sentot Novianto (Universitas Mercu Buana, 2024)
This study evaluates the performance of the condenser at the Cilegon Combined Cycle Power Plant (CCPP) using the Logarithmic Mean Temperature Difference (LMTD) method to measure the heat transfer rate. Routine maintenance carried out on the condenser in the form of cleaning the condenser water box and condenser tube from garbage and crust on the condenser tube wall. Currently, condenser maintenance follows a routine schedule that is tied to steam turbine maintenance, without taking actual condenser performance into account. This can lead to inefficiencies and unnecessary downtime. The goal of this research is to assess the heat transfer rate of the condenser before and after maintenance to judge its effectiveness. Data on temperature changes were gathered in June 2023, before maintenance, and again in July 2023, after an overhaul. The analysis shows that the heat transfer rate increased from 51,362,294.48 kcal/h to 127,246,219.7 kcal/h, while the LMTD value rose from 0.76°C to 1.86°C. Based on these results, the study suggests a new approach to maintenance that focuses on performance. Specifically, maintenance should be done when the heat transfer rate drops below 110,000,000 kcal/h. This approach will help ensure the condenser works at its best, improve the plant's overall efficiency, and prevent the need for unnecessary maintenance. By aligning maintenance with performance data, the plant can boost output while lowering costs and downtime.